The effect of exogen glutathione administration on the gastric mucosal barrier in rats under stress - Zeki KANAY; Cemil SERT; Birgül IŞIK; Doğan KURT; Cihat GÜZEL; Nuriye METE (Turkish Journal of Gastroenterology, 2019)
-